The Effect of Interactive Web-Based Learning (LWL) Model on Learning Outcomes Students with Visual Impairment and Students with Hearing Impairment at Universitas Islam Nusantara - Teti Ratnawulan; Prinanda Gustarina Ridwan; Yoga Budi Santoso; Eka Yuli Astuti; Emay Mastiani; Indiah Wisjnu Sulistyorini; Argiasri Mustika; Panji Romadhona (Journal of ICSAR, 2021)
Learning allows all students to be able to access education, including students with special needs. In the current pandemic, all learning activities are converted into online. However, students with special needs, especially blind and deaf students, have difficulty adapting and accessing learning using e-learning. It causes difficulties in understanding the contents of the material, and applications used cannot fully accommodate the needs of blind and deaf children. It has an impact on decreasing learning outcomes. The method used in this study uses a Research and Development (R&D) approach with an exploratory mixed-method research design. The subjects of this study were blind students (7 people) and deaf students (3 people) special education department in Uninus. The results showed that the Interactive Web-Based Learning (IWL) learning model had a good effect on the learning outcomes of blind and deaf students, especially in the physiology analysis subject for children with special needs and the growth and development of children with special needs. With the Interactive Web-Based Learning (IWL) learning model, it is hoped that blind and deaf students can explore more in online-based learning.